Site Selection for Future Mobility Hubs in Melbourne: A Multicriteria Location-Allocation Analysis - Allan Pimenta; Ulfah Rahmah; Mahesha Jayawardhena; Liton Kamruzzaman (Findings)
Mobility hubs (MHs) are places offering access to various modes of transport along with enhanced facilities to provide integrated and seamless travel. This study proposes a method to find optimum locations for the planning and development of MHs using Greater Melbourne as a case. Our analysis focuses on 222 existing train stations. We identified 18 stations that meet our operational definition of a mobility hub -- i.e., providing interchange facilities for trains, bus/tram, and shared mobility services. The remaining 204 stations were considered as potential candidates for future mobility hubs. These candidates were assessed using location-allocation analysis that optimizes their access for general public, students and commuters travelling by four different modes (car, bike, e-scooter and walking). The shortlisted stations were ranked using a multicriteria scoring system. The analysis resulted in 62 sites with high potential to develop as future mobility hubs.